Model predictive control-based direct torque control for matrix converter-fed induction motor with reduced torque ripple - Hanbing Dan; Peng Zeng; Wenjing Xiong; Meng Wen; Mei Su; Marco Rivera (CES Transactions on Electrical Machines and Systems, 2021)
To reduce the torque ripple in motors resulting from the use of conventional direct torque control (DTC), a model predictive control (MPC)-based DTC strategy for a direct matrix converter-fed induction motor is proposed in this paper. Two new look-up tables are proposed, these are derived on the basis of the control of the electromagnetic torque and stator flux using all the feasible voltage vectors and their associated switching states. Finite control set model predictive control (FCS-MPC) has then been adopted to select the optimal switching state that minimizes the cost function related to the electromagnetic torque. Finally, the experimental results are shown to verify the reduced torque ripple performance of the proposed MPC-based DTC method.